Prevalence of depression and anxiety among IIUM pre-clinical medical students during COVID 19 pandemic - Shaik Mohd Nizam, Nur Alia Iman; Razman, Amalia Izzati; Abdullah, Muhammad Haikal; Ahmad Ashhar, Muhammad Ikmal Arif; Ahmad Haridan, Ahmad Zhareff Emir; Nor Azlan, Nur Khairunnisa; Mohamad, Mohammad Muaz; Shahrir, Shahida Athirah; Anuar, Muhammad Ashraf Fithri; Johari, Muhammad Luqman ‘Afif; Zulkifli, Ahmad Najmi Abid; Zamani, Muhammad Razin; et al. (2021)
Given the tough nature of studying medicine, medical students are at higher risk of developing mental health-related issues such as depression and anxiety than the general public. The worries about what the future holds, lack of social interactions due to shifting towards online learning, and being confined inside the house for a long period of time due to government-imposed lockdown, might negatively affect medical students’ state of mind. This study was done to determine the prevalence of depression and anxiety among International Islamic University Malaysia (IIUM) preclinical medical students during COVID-19. A cross sectional study involving Year 1 (n=77) and Year 2 (n=81) medical students of IIUM was conducted from July till August 2020, and they were recruited to answer a self-administered online survey. This study was done in accordance with terms stipulated by the institutional ethical committee (Research ID: 735). The Generalized Anxiety Disorders Scale (GAD-7) and Well Being Index (WHO-5) scores were used to assess the level of anxiety and depression among the students respectively. The data were analysed using IBM SPSS Statistics 26 (IBM, New York). From 158 respondents, 27.8% of the students experienced depression, while 86.7% of the students flagged symptoms of anxiety. In accordance with this outcome, the concern about their physical well-being, social relationship and ffectiveness of online learning during this pandemic crisis are among the factors that might contribute to the increase of depression and anxiety among the students. This study has concluded that IIUM medical students showed an increased risk of suffering from depression and anxiety during COVID-19 era. It is highly suggested that proper interventions such as university support group online gathering, interactive online learning and gamification, and promotion of online counselling be administered in order to preserve good mental health of medical students during this pandemic